2019
DOI: 10.1088/1755-1315/301/1/012053
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties and volatile compounds of beef flavors produced by direct extrusion

Abstract: Beef flavors were formed by mixing amino acid, sugar, and wheat flour via the efficient and continuous direct extrusion process. The effect of the extrusion temperature of zone 1, at 80, 100 and 120°C, on the color, solubility, and sensory properties of the beef flavors obtained was investigated. Acceptability of extruded beef flavors, both in powder and liquid forms, was tested compared to the control, which was a commercial beef flavor prepared by the traditional method (boiling and reflux). Volatile compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Sakunwaropat et al. (2019) identified 13 volatile compounds from the extruded process flavorings from mixing amino acid with reducing sugar and wheat flour as a carrier. They also found methanethiol as a key component contributing to stewed beef and ground beef, as well as 2‐furancarboxaldehyde, 3‐(methylthiol)‐propanal, 2‐ (methylthiol) methyl‐furan in the products.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sakunwaropat et al. (2019) identified 13 volatile compounds from the extruded process flavorings from mixing amino acid with reducing sugar and wheat flour as a carrier. They also found methanethiol as a key component contributing to stewed beef and ground beef, as well as 2‐furancarboxaldehyde, 3‐(methylthiol)‐propanal, 2‐ (methylthiol) methyl‐furan in the products.…”
Section: Resultsmentioning
confidence: 99%
“…Methanethiol compound could be generated from Maillard reaction of methionine with monosaccharides and present powerful onion cabbage odor at odor threshold of 0.02 to 4 ppb in water (Buettner & Schieberle, 2001). Sakunwaropat et al (2019) identified 13 volatile compounds from the extruded process flavorings from mixing amino acid with reducing sugar and wheat flour as a carrier. They also found methanethiol as a key component contributing to stewed beef and ground beef, as well as 2-furancarboxaldehyde, 3-(methylthiol)propanal, 2-(methylthiol) methyl-furan in the products.…”
Section: Identification Of Volatile Compoundsmentioning
confidence: 99%
See 3 more Smart Citations